2018
DOI: 10.1111/his.13690
|View full text |Cite
|
Sign up to set email alerts
|

Pathologist's health‐care value in the triage of Oncotype DX® testing: a value‐based pathology study of tumour biology with outcomes

Abstract: This unique study demonstrates that (i) pathologists add great value to triage breast cancer for GEPT; and (ii) can identify prospectively low-grade tumour biology with high sensitivity and high specificity for those cases which do not require chemotherapy (RS < 25) using MS and hormone receptor content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…Others have also reported significant cost savings with the use of MEs [ 37 , 38 , 40 ]. This should alarm integrated health systems (provider and insurer) that want to move toward value-based system [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others have also reported significant cost savings with the use of MEs [ 37 , 38 , 40 ]. This should alarm integrated health systems (provider and insurer) that want to move toward value-based system [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies implied that ordering of ODX test for every eligible ERþ/HER2-negative/lymph node-negative female patients with invasive breast carcinoma might not contribute to clinical management decisions. Some of these studies suggested that analysis of some of the clinicopathologic data available from pathology reports may select patients for which ODX test results were highly predictable and, therefore, the test could be safely and appropriately avoided [33,34]. We previously developed a "user friendly" nomogram/calculator [14] as a surrogate prediction model for the ODX score.…”
Section: Discussionmentioning
confidence: 99%
“…First, we performed a detailed review of cases that showed ODX RS of ≤25 with a special focus on cases with RS of ≤10. We identified that up to a third of cancers with RS of ≤10 are of low-grade special subtype (such as tubular, cribriform, mucinous, classic lobular), and most others are enriched in high hormone receptor content and almost always have a mitosis score of 1 36 . This helped us design an algorithm based on MEs and mitosis score, which we prospectively applied to cases requested for clinical testing.…”
Section: Validation and Magee Decision Algorithmmentioning
confidence: 99%
“…We identified that up to a third of cancers with RS of ≤10 are of low-grade special subtype (such as tubular, cribriform, mucinous, classic lobular), and most others are enriched in high hormone receptor content and almost always have a mitosis score of 1. 36 This helped us design an algorithm based on MEs and mitosis score, which we prospectively applied to cases requested for clinical testing. The prospective value study included all clinical requests for ODX testing from the latter half of 2016 to the first quarter of 2018 at our center, resulting in a total of 205 cases.…”
Section: Validation and Magee Decision Algorithmmentioning
confidence: 99%